2017
DOI: 10.1021/acs.inorgchem.7b00902
|View full text |Cite
|
Sign up to set email alerts
|

[2 + 2]-type Reaction of Metal–Metal σ-Bond with Fullerene Forming an η1-C60 Metal Complex: Mechanistic Details of Formation Reaction and Prediction of a New η1-C60 Metal Complex

Abstract: C[CpRu(CO)] is only one transition-metal fullerene complex with pure η-coordinated bonds, which was recently synthesized through the reaction between dinuclear Ru complex [CpRu(CO)] and C. Though new properties can be expected in the η-coordinated metal-fullerene complex, its characteristic features are unclear, and the [2 + 2]-type formation reaction is very slow with a very small yield. A density functional theory study discloses that the η-coordinated bond is formed by a large overlap between the Ru d orbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
0
9
2
Order By: Relevance
“…The HOMO of Y@ C 2 v (9)-C 82 [Re­(CO) 5 ] is mainly composed of the SOMO of Y@ C 2 v (9)-C 82 . These results are different from the cases of another η 1 -coordinated complex C 60 [CpRu­(CO) 2 ] 2 and the typical η 2 -coordinated complex Pt­(PMe 3 ) 2 C 60 , in which the transition-metal groups have large contributions to their HOMOs.…”
Section: Results and Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…The HOMO of Y@ C 2 v (9)-C 82 [Re­(CO) 5 ] is mainly composed of the SOMO of Y@ C 2 v (9)-C 82 . These results are different from the cases of another η 1 -coordinated complex C 60 [CpRu­(CO) 2 ] 2 and the typical η 2 -coordinated complex Pt­(PMe 3 ) 2 C 60 , in which the transition-metal groups have large contributions to their HOMOs.…”
Section: Results and Discussioncontrasting
confidence: 70%
“…The C 60 {η 1 -Ru­(CO) 2 (η 5 -C 5 H 5 )} 2 complex was synthesized and characterized, but the reaction was difficult and the yield of product was very small . Theoretical studies revealed that these two reactions have large energy barriers and the products are not thermodynamically favored …”
Section: Introductionmentioning
confidence: 99%
“…Exohedral and/or endohedral modification of fullerenes with metallic species are feasible ways to change their intrinsic properties so as to create components useful in spintronics and molecular devices/machines. The organometallic chemistry of fullerenes originating from the landmark compound C 60 O 2 OsO 2 (py) 2 has blossomed a great deal during the past few years, but a majority of the organometallic complexes reported so far have involved either η 2 attachment of a transition metal to a [6,6]-bond or an η 5 coodination to a pentagonal ring because such η 2 and η 5 coordinations can afford stable complexes for further characterizations. However, pursuit of the prototypical η 1 -coordinated organometallic complexes of fullerenes is not straightforward because most of them are still mixed with η 2 or η 5 bonding fashions. C 60 [Re­(CO) 5 ] 2 was proposed to bear the pure η 1 coordination fashion, but it decomposes into the corresponding precursors even at room temperature. To the best of our knowledge, the only example with pure η 1 coordination fashion identified so far is the ruthenium complex of C 60 , namely [(η 5 -C 5 H 5 )­Ru­(CO) 2 -η 1 ] 2 -C 60 , where two Ru­(CO) 2 groups attach to the cage in a [1,4]-pattern . Still, a complex with only a single metal–cage bond is not available now for fullerenes.…”
Section: Introductionmentioning
confidence: 99%
“…For EMFs lacking the sumanene unit, such as Sc 3 N@C 80 , our group has developed an efficient tungsten-coordination reaction to produce the η 2 complexes of EMFs . However, the simplest η 1 -coordinated complexes of EMFs with only one metal–cage bond have not been reported so far, probably due to the low stability of such complexes, similar to that of the corresponding C 60 analogues. …”
Section: Introductionmentioning
confidence: 99%
“…Due to the two electron-transfer from Eu onto the cage (Table S2 †) and the moving state of the Eu ion in Eu@C 2 (5)-C 82 /Eu@C 2 (13)-C 84 , it is reasonable to consider [C 2 (5)-C 82 ] 2À and [C 2 (13)-C 84 ] 2À as the prototypes. The coordination reactions of alkenes 18 and C 60 25,26 with metallic complexes can be well understood by considering the frontier orbitals where the LUMO of alkenes/C 60 accepts electrons from metallic complexes to form coordination bonds. Accordingly, the LUMO distributions of [C 2 (5)-C 82 ] 2À and [C 2 (13)-C 84 ] 2À along with the HOMO distribution of the tungsten addend are calculated (Fig.…”
Section: Regiochemical Control Of Exohedral Addition By Internal Metamentioning
confidence: 99%